The Impact of Corporate Social Responsibility and Capital Intensity on Tax Avoidance - Septianti, Alda; Nur Khairin, Fibriyani (Fakultas Ekonomi dan Bisnis Universitas Mulawarman, 2025)
This study aims to analyze the effect of Corporate Social Responsibility (CSR) and Capital Intensity on tax avoidance in mining sector companies listed on the Indonesia Stock Exchange (IDX) in the 2018-2022 period. The research method used is multiple regression analysis with a sample of 18 companies with a total of 5 years of observation. The independent variables in this study are CSR measured by the amount of expenditure and capital intensity measured by the ratio between fixed assets and total assets. While the dependent variable is tax avoidance measured using the level of tax ratio. The results show that CSR has a negative effect on tax avoidance, which indicates that companies that carry out CSR activities show corporate responsibility, but there is also the possibility that the company is doing tax avoidance. On the other hand, capital intensity has a negative effect on tax avoidance, which means that not all companies deliberately utilize fixed asset depreciation costs to reduce tax avoidance. The findings provide insights into the important role of social responsibility and capital intensity in influencing corporate tax strategy in the Indonesian mining sector